2014
DOI: 10.3389/fpls.2014.00405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and the regulatory B-subunit composition of protein phosphatase 2A on the susceptibility of Arabidopsis thaliana to aphid (Myzus persicae) infestation

Abstract: The interactions between biotic and abiotic stress signaling pathways are complex and poorly understood but protein kinase/phosphatase cascades are potentially important components. Aphid fecundity and susceptibility to Pseudomonas syringae infection were determined in the low light-grown Arabidopsis thaliana wild type and in mutant lines defective in either the protein phosphatase (PP)2A regulatory subunit B'γ (gamma; pp2a-b'γ) or B'ζ (zeta; pp2a-b'ζ1-1 and pp2a-b'ζ 1-2) and in gamma zeta double mutants (pp2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…Likewise, mutations affecting members of the FASS/TON2 clade cause strong phenotypes due to defects in preprophase band formation (McClinton and Sung, 1997;Camilleri et al, 2002;Wright et al, 2009). Consistent with the functional specificity of plant PP2A B subunit isoforms, b5/b9g mutants have phenotypes distinct from b8/b9z mutants (Rasool et al, 2014;Konert et al, 2015). However, additional data suggest varying degrees of functional overlap among plant PP2A subunit isoforms.…”
Section: Retention Of Duplicated Pp2a Subunit Genesmentioning
confidence: 82%
“…Likewise, mutations affecting members of the FASS/TON2 clade cause strong phenotypes due to defects in preprophase band formation (McClinton and Sung, 1997;Camilleri et al, 2002;Wright et al, 2009). Consistent with the functional specificity of plant PP2A B subunit isoforms, b5/b9g mutants have phenotypes distinct from b8/b9z mutants (Rasool et al, 2014;Konert et al, 2015). However, additional data suggest varying degrees of functional overlap among plant PP2A subunit isoforms.…”
Section: Retention Of Duplicated Pp2a Subunit Genesmentioning
confidence: 82%
“…10 The Arabidopsis B'g knockdown mutant showed constitutive induction of salicylic acid-and jasmonic aciddependent defense pathways, and the mutant was more resistant to bacterial, fungal, and aphid infections than wild type plants. 11,12 Moreover, B'g was proposed to have a role in daylength-dependent oxidative stress. 13 Another interesting study revealed a role for PP2A in negative regulation of PTI.…”
Section: B'h Subfamily Members Are Involved In Negativementioning
confidence: 99%
“…Therefore, photosynthetic machinery is a fine-tuneable mechanism whose functioning cannot be considered only in the context of plant productivity, as it seems to play a dominant role in the regulation of plant stress resistance Trotta et al 2014). Increasing evidence reinforces the profound effect of light on plant resistance/susceptibility to biotic stresses (Göhre et al 2012;Hua 2013;Rasool et al 2014;Roden and Ingle 2009;Szechyńska-Hebda et al 2010). This regulation is connected not only with light pre-treatment (Szechyńska-Hebda et al 2010), but is also dependent on the circadian clock (Bhardwaj et al 2011;Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This response is accompanied by alterations in ROS and redox signals, and the induction of glutathione, salicylic acid (SA), and ethylene (ET) in both local and systemic leaves (Mühlenbock et al 2008;Szechyńska-Hebda et al 2010). Moreover, it was demonstrated that high-light pre-exposure caused enhanced resistance to aphid infestation in wild-type plants and in mutant lines defective in the composition of B-subunits on the trimeric protein phosphatase 2A (PP2A) holoenzymes (Rasool et al 2014).…”
Section: Introductionmentioning
confidence: 99%